Prevalence of intestinal parasites among gastrointestinal patients in Hun City, Libya: A cross-sectional study - zaed, Hana Abd Alsalam; Elgobbi, Ali Mohamed (Sirte Journal of Medical Sciences, 2025)
Background:This cross-sectional study aimed to assess the prevalence and distribution of intestinal parasites among patients attending Al-Masra'a Clinic in Hun city, Aljufra, Libya,from January 2021 to December 2023.. Methods:A total of 1,079 stool samples were collected from gastrointestinal patients. Sociodemographic data and risk factors were gathered using a structured questionnaire. Stool samples were examined using light and dark ground microscopy, direct smear techniques with normal saline and Lugol’s iodine, and the formalin-ether concentration technique. Ziehl-Nielsen staining was used for microscopic differentiation of parasite developmental forms. Data were analysed using SPSS (version 24), with descriptive statistics and Chi-square tests employed to identify significant associations. Results:Intestinal parasites were detected in 13.3% (144/1,079) of the patients, with a significant difference (P=0.02). Males had a higher infection rate (68.75%) compared to females (31.25%), with a significant difference (P=0.04). The highest prevalence was observed in individuals under 20 years (48.6%), followed by the 20-40 age group (22.2%). Entamoeba histolytica was the most common parasite (73.61%), followed by Giardia lamblia (10.41%) and Entamoeba coli (7.63%). Co-infections were rare (6.25%). The prevalence of infections declined over the study period, from (11.6%) in 2021 to (7.4%) in 2023 (P=0.02). Rural areas had a significantly higher prevalence (84.02%) compared to urban areas (15.97%), with a significant difference (P=0.04). Conclusion:The study highlights the need for targeted public health interventions, particularly in rural areas, to improve sanitation, health education, and access to healthcare. Enhanced water quality and hygiene practices are crucial to reducing the burden of intestinal parasitic infections in the region.